Proceedings of the 10th EAI International Conference on Performance Evaluation Methodologies and Tools 2017
DOI: 10.4108/eai.25-10-2016.2266606
|View full text |Cite
|
Sign up to set email alerts
|

A Queueing Network Model for Performance Prediction of Apache Cassandra

Abstract: NoSQL databases such as Apache Cassandra have attracted large interest in recent years thanks to their high availability, scalability, flexibility and low latency. Still there is limited research work on performance engineering methods for NoSQL databases, which yet are needed since these systems are highly distributed and thus can incur significant cost/performance trade-offs. To address this need, we propose a novel queueing network model for the Cassandra NoSQL database aimed at supporting resource provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…We have observed that the demand D changes almost linearly with the number of active nodes, as shown in Figure 5. This is mainly due to the increasing number of read requests issued by the request coordinator [28]. In our tests, each additional active node increases D on average by α = 10%.…”
Section: A Workload Forecastingmentioning
confidence: 85%
“…We have observed that the demand D changes almost linearly with the number of active nodes, as shown in Figure 5. This is mainly due to the increasing number of read requests issued by the request coordinator [28]. In our tests, each additional active node increases D on average by α = 10%.…”
Section: A Workload Forecastingmentioning
confidence: 85%
“…For example, a job that visits multiple times the same node, requesting different execution requirements at each visit, may be modelled by assuming that the job switches class in-between visits. Distributed NoSQL databases such as Apache Cassandra provide an example, in which class-switching can be used to express a workflow of execution through multiple nodes in order to retrieve the data needed by a query for its completion [DCS17].…”
Section: Discussionmentioning
confidence: 99%
“…The Jensen Shannon divergence is bounded between 0 ≤ D JS ≤ 1 In this section, we illustrate the Cassandra model used for evaluating the SD algorithm. This is a simplified version of the model presented in [5]. With the aim to reduce the model complexity and the system state space, we have developed a model able to support only the Consistency Level ONE.…”
Section: B Divergence Measuresmentioning
confidence: 99%
“…Each Cassandra node uses the processor sharing (PS) scheduling policy. All the other stations used in [5], such as the networks and disk queues, have been grouped in a single infinite queue (or infinite server), called 'Net' positioned right after the workload generator. In addition, the workload generator has also been modelled as an infinite server.…”
Section: B Divergence Measuresmentioning
confidence: 99%
See 1 more Smart Citation